A Flexible Fiber‐Based Supercapacitor–Triboelectric‐Nanogenerator Power System for Wearable Electronics. (14th July 2015) - Wang, Jie; Li, Xiuhan; Zi, Yunlong; Wang, Sihong; Li, Zhaoling; Zheng, Li; Yi, Fang; Li, Shengming; Wang, Zhong Lin
<x xml:space="preserve">Abstract</x> A flexible self‐charging power system is built by integrating a fiber‐based supercapacitor with a fiber‐based triboelectric nanogenerator for harvesting mechanical energy from human motion. The fiber‐based supercapacitor exhibits outstanding electrochemical properties, owing to the excellent pseudocapacitance of well‐prepared RuO2·xH2O by a vapor‐phase hydrothermal method as the active material. The approach is a step forward toward self‐powered wearable electronics.